Antimicrobial peptide GL13K-Modified titanium in the epigenetic regulation of osteoclast differentiation via H3K27me3 - Gao, Yuerong; Lai, Yingzhen; Wang, Hong; Su, Jingjing; Chen, Yan; Mao, ShunJie; Guan, Xin; Cai, Yihuang; Chen, Jiang (Frontiers in Bioengineering and Biotechnology, 2024)
Implant surface designs have advanced to address challenges in oral rehabilitation for healthy and compromised bone. Several studies have analyzed the effects of altering material surfaces on osteogenic differentiation. However, the crucial role of osteoclasts in osseointegration has often been overlooked. Overactive osteoclasts can compromise implant stability. In this study, we employed a silanization method to alter pure titanium to produce a surface loaded with the antimicrobial peptide GL13K that enhanced biocompatibility. Pure titanium (Ti), silanization-modified titanium, and GL13K-modified titanium (GL13K-Ti) were co-cultured with macrophages. Our findings indicated that GL13K-Ti partially inhibited osteoclastogenesis and expression of osteoclast-related genes and proteins by limiting the formation of the actin ring, an important structure for osteoclast bone resorption. Our subsequent experiments confirmed the epigenetic role in regulating this process. GL13K-Ti was found to impact the degree of methylation modifications of H3K27 in the NFATc1 promoter region following RANKL-induced osteoclastic differentiation. In conclusion, our study unveils the potential mechanism of methylation modifications, a type of epigenetic regulatory modality, on osteoclastogenesis and activity on the surface of a material. This presents novel concepts and ideas for further broadening the clinical indications of oral implants and targeting the design of implant surfaces.